REGULATORY FOCUS DAN EMPLOYEE WELL-BEING USTADZ/USTADZAH DI PONDOK PESANTREN - Diana, Huriah Nurul (Jurnal Riset Psikologi, 2023)
Abstract: Regulatory Focus and Employee Well-Being of Ustadz/Ustadzah in Islamic Boarding School. This study aims to find out whether there is a contribution of regulatory focus to employee well-being. Regulatory focus is a multi-dimensional construct consisting of prevention focus and promotion focus. Respondents consisted of 111 teachers at Pondok Pesanten Thawalib Parabek Bukittinggi. Using a quantitative approach with survey methods. Data analysis was performed with multiple linear regression. The results of this study indicate that Prevention Focus and Promotion Focus contribute as much as 6.5% together.